2023
DOI: 10.14716/ijtech.v14i4.5678
|View full text |Cite
|
Sign up to set email alerts
|

Baby Incubator with Overshoot Reduction System using PID Control Equipped with Heart Rate Monitoring Based on Internet of Things

Abstract: Factors causing premature infant mortality include the lack of simple care and inadequate equipment such as a baby incubator. Premature babies are very susceptible to heart disorders, including congenital heart defects. Congenital heart defects can cause a fetus to be born prematurely. The current research related to this matter was further conducted, aiming to develop a baby incubator with an overshoot reduction system specifically for babies with heart defects that can be monitored remotely using an IoT syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…In the measurement results, it was found that the pulse rate reached an error value of around 0.6 with a tolerance of 5% or 5 BPM. According to Matthew E. Wieler [19], the results of his research obtained an error value of around 0.53%, while other studies also attained an error value of 0.37% [20], 0.87% [21] <1.702% [22], 2.702% [23], and 3.23% [24]. The allowable error value for patient care was less than 5%.…”
Section: Discussionmentioning
confidence: 90%
“…In the measurement results, it was found that the pulse rate reached an error value of around 0.6 with a tolerance of 5% or 5 BPM. According to Matthew E. Wieler [19], the results of his research obtained an error value of around 0.53%, while other studies also attained an error value of 0.37% [20], 0.87% [21] <1.702% [22], 2.702% [23], and 3.23% [24]. The allowable error value for patient care was less than 5%.…”
Section: Discussionmentioning
confidence: 90%
“…The previous research on incubators served as a reference for the development of this study. Irianto et al in 2023 [7] focused on monitoring and controlling the temperature and heart rate of premature babies using IoT and PID control for temperature regulation. Furthermore, Alimuddin et al [6] worked on  ISSN: 2502-4752 Indonesian J Elec Eng & Comp Sci, Vol.…”
Section: Related Workmentioning
confidence: 99%
“…Additionally, for monitoring systems, message queue telemetry transport (MQTT) protocol with a third-party IoT broker has been used, where the provided features are still limited. In previous research, the focus was on using fuzzy and PID algorithms to control the system to maintain temperature as desired [6], [7]. However, some studies only concentrated on monitoring temperature and humidity without any systematic control.…”
mentioning
confidence: 99%